Changing Propensity to Die at Home for People with Cancer in Scotland 2001-2011: Evidence from A Data Linkage Study - Iain Atherton; Anna Schneider; David Henderson (International Journal of Population Data Science, 2020)
Introduction The proportion of deaths at home amongst cancer patients has increased internationally in recent years. This trend has become evident in Scotland. Underlying reasons are unclear and may include changing hospital policy decisions and changing social and demographic composition of the population.